Qualitative assessment of the patient experience of primary hyperoxaluria type 1: an observational study - David Danese; Diana Goss; Carla Romano; Catherine Gupta (BMC Nephrology, 2023)
Abstract Background Without effective intervention, primary hyperoxaluria type 1 (PH1) causes oxalate-induced kidney damage, leading to end-stage kidney disease and serious complications throughout the body. Although PH1 carries a heavy burden that impacts quality of life, literature on the experiences of those living with PH1 and caring for patients with PH1 is limited. This study aimed to describe the diagnostic journey in PH1 and characterize patients’ and caregivers’ self-reported experiences throughout the disease course. Methods This was an observational study involving in-depth, semi-structured telephone interviews. Dominant trends were assessed using constant comparative analysis to identify themes in interviewees’ descriptions of their experiences. Individuals aged ≥ 12 years and caregivers of children aged 6–17 years with genetically confirmed PH1 were eligible. Informed consent/assent and ability to read and speak English were required. Results Interviewees (16 patients, 12 caregivers) reported a prolonged diagnostic journey due to low disease awareness, among other factors. Upon diagnosis, PH1 was frequently symptomatic, typically involving kidney stone-related symptoms but also potentially symptoms arising beyond the kidneys. PH1 most commonly led to worry and social impairment in adolescents, impaired physical function in adults, and a range of impacts on caregivers. In late-stage disease, dialysis was the most burdensome aspect of living with PH1 (due to time requirements, limitations from living with a catheter, etc.), and this burden was exacerbated by the COVID-19 pandemic. Benefits desired from PH1 management included reductions in laboratory measures of oxalate burden, kidney stone and urination frequency, and oxalate-related skin ulcers. Conclusions PH1 greatly impacts patients’ and caregivers’ lives, primarily due to burdensome disease manifestations and associated emotional, physical, and practical impacts, as well as disease management challenges – particularly those related to dialysis in late-stage disease.